Unlocking the Taxpayer Compliance Enigma: The Moderating Impact of Ownership Profiles - Sadalia, Isfenti; Muchtar, Yasmin Chairunisa; Hasibuan, Beby Kendida; Irawati, Nisrul; Widiastuti, Tika (Journal of Ecohumanism, 2024)
This research aims to analyze the factors that influence MSME tax compliance in Indonesia. Even though MSMEs make a significant contribution to the economy, their level of tax compliance is still low. Several factors that influence MSME tax compliance include the quality of tax services, tax knowledge, and business ownership characteristics. Previous research results show that there is a gap between potential and actual tax revenue from MSMEs. Apart from that, factors such as dissatisfaction with public services, infrastructure inequality and corruption also pose challenges in increasing tax compliance. This research concludes that improving the quality of tax services, increasing tax knowledge, and improving the overall tax administration system can increase MSME tax compliance.